Decoding Filipino Representation in Project Nightfall's Videos: a Critical Discourse Analysis - Bebis, Ma. Kyryll Manaog; Fajardo, Dan Fereth (SIGEH ELT : Journal of Literature and Linguistics, 2024)
This research aimed to decode Filipino representations from the videos of Project Nightfall, a social media channel with millions of followers all over its social media platform that produces videos relative to society’s interest. The rising numbers of Vlogs associated with Pinoy contents produced by foreigners from different social media channels urged the study to work on identifying how Filipinos are represented in Vlogs from the point of view of these social media content creators. The study used Fairclough’s Three-Dimensional Framework of Critical Discourse Analysis with three fundamental stages in the study of discourse: the Description or the study of the properties of text, the Interpretation of discursive practices, and the Explanation that deals with Social Practice Analysis. The research selected three videos from the Facebook Page of Project Nightfall. Relevant texts were extracted from the manual transcripts for the analysis. From the research findings, the text is observed to have produced description, assertion and affirmation in the most parts which demonstrates a social practice of promoting culture. There are few numbers of negative Filipino representations depicted from the text including how Filipinos are represented to be financially and emotionally struggling. Filipinos are seen as providers, and described short in height. On the other hand, Filipinos are represented to be selfless, compassionate, resourceful, respectful, expressive, optimistic, bubbly, culture-bound, have active lifestyle, have values of teamwork and spirit of community. Filipinos are also defined as artists, singers, and sports lover from the context of the videos selected.